Recent progress in the synthesis of poly(organo)phosphazenes and their applications in tissue engineering and drug delivery. (28th February 2018) - Khan, R U; Wang, L; Yu, H; Zain-ul-Abdin,; Akram, M; Wu, J; Haroon, M; Ullah, R S; Deng, Zh; Xia, X
Abstract: It is a highly desirable goal of researchers to develop effective biomaterials with minimum recovery time and affordable treatment expense for tissue engineering and drug delivery. In this scenario, numerous synthetic and natural polymers have been used. Among those synthetic polymers, polyorganophosphazenes (POPs) have got much attention as highly promising candidates for applications in tissue engineering and drug delivery. Polyorganophosphazenes are hybrid polymers containing inorganic backbone consisting of alternating nitrogen and phosphorus atoms with two organic side groups. POPs possess a wide range of unique properties, i.e ., synthetic flexibility, biocompatibility, osteocompatibility, osteoinductivity, sustainability and degradability into harmless end products with predictable degradation rate and adjustable mechanical strength. Moreover, their tunable hydrophilic/hydrophobic and stimuli responsive properties add extra points to their use in biomedical applications. In addition, their various polymeric forms, i.e ., microspheres, nano/microfibres, micelles, membranes, polymersomes, hydrogels and nano-conjugate linear polymers provide different carriers to efficiently deliver various hydrophilic/hydrophobic therapeutic agents both in vitro and in vivo . This review focuses on the most recent progress that has been made in the synthesis and applications of POPs in tissue engineering and their different polymeric forms used for drug delivery. Moreover, we have also summarized the effect of different side groups on the overall efficiency of POPs. The bibliography includes 239 references.